In situ leading-edge-induced damages of melting and cracking W/Cu monoblocks as divertor target during long-term operations in EAST. (1st May 2022) - Zhu, Dahuan; Li, Changjun; Gao, Binfu; Ding, Rui; Wang, Baoguo; Guo, Zongxiao; Xuan, Chuannan; Yu, Baixue; Lei, Yang; Chen, Junling; EAST Team, the
Abstract: The leading-edge-induced thermal loading effect due to assembly tolerance between neighboring castellated plasma-facing components is a critical issue in fusion devices. Actively cooled ITER-like W/Cu monoblocks were successfully installed for the upper divertor target in EAST which significantly increases the performance of the divertor power exhaust. The misalignment between neighboring monoblocks was formed inevitably during manufacturing and assembly processes, providing a possibility to demonstrate the leading-edge-induced thermal damage. Indeed, the leading-edge-induced melting phenomena of W/Cu monoblocks on upper divertor targets were observed using CCD a camera during plasma discharges with a large number of droplets ejected from the divertor target, which were also identified at the leading edges of W/Cu monoblocks. Not only that, but also many macro cracks with widths of ∼70 μ m and depths of <5 mm along radial and toroidal directions were also found universally at the leading edges of W/Cu monoblocks by post-mortem inspection after plasma campaigns. Thermal–mechanical analysis by means of finite element simulation demonstrated that the maximum temperature could reach W melting point under the current projected heat load of ∼3 MW m −2 on flat top surface with large misalignment up to 3 mm at the leading edges. Meanwhile, the high temperature also induced high thermal stress and strain concentration at the center of leading edges, at which thermal fatigue cracking could be initially generated. Such type of cracks at leading edges on W/Cu monoblocks may be unavoidable due to long-term, pulsed fatigue effects. However, the influence of these cracks seems to be acceptable thanks to the limited propagated distance due to the self-castellation effect, which still needs long-term tracking. The in situ leading-edge-induced melting and cracking damage on W/Cu monoblocks of the EAST upper divertor target provides significant insight on understand the leading-edge-induced thermal effect in ITER and future fusion devices.